2020
DOI: 10.1002/prp2.667
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between Angiotensin receptors ligands: Role of Angiotensin‐(1‐7) in modulating AT2R agonist response on nitric oxide in kidney cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…For example, some authors shown that Ang‐(1‐7) can bind to the AT 2 receptor (Bosnyak et al, 2011; Paz Ocaranza et al, 2020) or that AT 2 and Mas receptors can form functional heterodimer (Leonhardt et al, 2017). On the other hand, some studies showed that blocking the AT 2 receptor does not interfere with the actions mediated by Ang‐(1‐7) (Castro et al, 2005; Dharmani et al, 2007; Patel & Hussain, 2020). Therefore, these complex interactions between the components of the RAS need better clarification, both in understand these interactions in normal physiological function and to develop effective therapies to treat their dysregulation, in particular, in experimental and clinical asthma.…”
Section: An Overview: Renin‐angiotensin System In Asthmamentioning
confidence: 99%
“…For example, some authors shown that Ang‐(1‐7) can bind to the AT 2 receptor (Bosnyak et al, 2011; Paz Ocaranza et al, 2020) or that AT 2 and Mas receptors can form functional heterodimer (Leonhardt et al, 2017). On the other hand, some studies showed that blocking the AT 2 receptor does not interfere with the actions mediated by Ang‐(1‐7) (Castro et al, 2005; Dharmani et al, 2007; Patel & Hussain, 2020). Therefore, these complex interactions between the components of the RAS need better clarification, both in understand these interactions in normal physiological function and to develop effective therapies to treat their dysregulation, in particular, in experimental and clinical asthma.…”
Section: An Overview: Renin‐angiotensin System In Asthmamentioning
confidence: 99%